INFLUENCE OF CONTEMPORARY TOURISM INFRASTRUCTURE IN BOOSTING A COUNTRY'S TOURISM DEVELOPMENT (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This study examines the role of modern tourism infrastructure in increasing a country's tourism potential. Using a combination of regression analysis and correlation studies, we analyze key infrastructure factors that influence tourism growth. Data from multiple sources is used to provide empirical evidence of the relationship between infrastructure development and tourism expansion. The findings suggest that investment in modern transportation, accommodation, and digital infrastructure significantly impacts tourist arrivals and revenue generation.